Predictors of CBT Outcome in Older Adults with GAD - Hundt, Natalie E. (J Anxiety Disord, 2014)
The current study is a secondary analysis of data from a randomized controlled trial of CBT for late-life GAD (Stanley et al., 2014) which provided an opportunity to examine predictors of outcome among those who received CBT. Participants were 150 older adults who were randomized to receive 10 sessions of CBT. Completer analyses found that homework completion, number of sessions attended, lower worry severity, lower depression severity, and recruitment site predicted 6-month worry outcome on the PSWQ-A, whereas homework completion, credibility of the therapy, lower anxiety severity, and site predicted better 6-month anxiety outcome on the STAI-T. In intent-to-treat multivariate analyses, however, only initial worry and anxiety severity, site, and number of sessions completed predicted treatment outcome. These results are largely consistent with predictors of outcome in younger adults and suggest that lower initial symptom severity and variables consistent with greater engagement in treatment predict outcome.